Development and validation of a dietary assessment tool to determine dietary intake of people living in oesophageal cancer risk areas in the rural Eastern Cape of South Africa - Lombard, Martani Johanni (Division of Human Nutrition, 2015)
Rural areas in the Eastern Cape (EC) Province of South Africa have a high incidence of oesophageal cancer (OC). Amongst the known risk factors associated with the cancer is fumonisin exposure (a mycotoxin growing on maize), poor dietary habits and nutrient deficiencies. Little is known about the current dietary habits and nutrient intake of these people, and therefore maize consumption and fumonisins exposure.